TINJAUAN YURIDIS PERTANGGUNGJAWABAN KORPORASI DALAM PENAMBANGAN ILEGAL - Ade Budi Brilliant; Aniek Periani; Ikama Dewi Setia Triana; Wiwin Muchtar Wiyono; Elly Kristiani Purwendah (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2026)
Illegal mining has become a strategic agenda in achieving legal certainty, environmental protection, and optimizing state revenues, particularly in Indonesia. A study of corporate accountability in illegal mining in Indonesia is essential to ensure that all existing legal instruments are properly implemented. This research is a qualitative study using a normative legal research approach. The results show that most cases that have been legally binding place company directors or managers as defendants, rather than the corporation itself. This may be due to the following factors: it is easier for prosecutors to prove the guilt of management, proving individual guilt is simpler than proving the existence of corporate policies, and law enforcement in the mineral and coal sector is still oriented towards individual perpetrators.